Antifungal activity of eco-safe nanoemulsions based on Nigella sativa oil against Penicillium verrucosum infecting maize seeds: Biochemical and physiological traits - Mosa, Mohamed A.; Youssef, Khamis; Hamed, Said F.; Hashim, Ayat F. (Frontiers in Microbiology, 2023)
The main objectives of the current study were to produce a green Nigella sativa-based O/W nanoemulsion fungicides to protect maize seeds from P. verrucosum infection, to test their antifungal activity against P. verrucosum and to examine their effect on plant physiological parameters. Two nonionic surfactants namely Tween 20 and Tween 80 were used as emulsifying agents in these formulations. The oil phase was cold-pressed black seed (N. sativa) oil as it has distinct antifungal activity. The effect of sonication time and surfactant type on the mean droplet size, polydispersity index (PDI), and zeta potential of the nanoemulsions were determined by dynamic light scattering (DLS). Results indicated that both sonication time and emulsifier type had pronounced effects on the stability of O/W nanoemulsions with a small particle size range (168.6- 345.3 nm), acceptable PDI (0.181 to 0.353), and high zeta potential (-27.24  -48.82 mV). Tween 20 showed superior stability compared to Tween 80 nanoemulsions. The in vitro results showed that a complete inhibition of P. verrucosum-growth was obtained by 10_T80 and 10_T20 nanoemulsions at 100% concentration. All nanoemulsions had a positive effect on maize seed germination compared to untreated seeds and the chemical treatment. Nanoemulsions (10_T20 and 10_T80) were able to stimulate root and shoot length as compared to the chemical treatment. Seed treatment with 10_T80 nanoemulsion showed the highest AI and protease activity by 75% and 70%, respectively, as compared to the infected control. The produced nanoemulsions might provide an effective protectant coating layer for the stored maize seeds.